Neuroprotection mediated by the Wnt/Frizzled signaling pathway in early brain injury induced by subarachnoid hemorrhage - Wang, Yang (Neural Regen Res, 2019)
The Wnt/Frizzled signaling pathway participates in many inflammation-linked diseases. However, the inflammatory response mediated by the Wnt/Frizzled signaling pathway in experimental subarachnoid hemorrhage has not been thoroughly investigated. Consequently, in this study, we examined the potential role of the Wnt/Frizzled signaling pathway in early brain injury in rat models of subarachnoid hemorrhage. Simultaneously, possible neuroprotective mechanisms were also investigated. Experimental subarachnoid hemorrhage rat models were induced by injecting autologous blood into the prechiasmatic cistern. Experiment 1 was designed to examine expression of the Wnt/Frizzled signaling pathway in early brain injury induced by subarachnoid hemorrhage. In total, 42 adult rats were divided into sham (injection of equivalent volume of saline), 6-, 12-, 24-, 48-, 72-hour, and 1-week subarachnoid hemorrhage groups. Experiment 2 was designed to examine neuroprotective mechanisms of the Wnt/Frizzled signaling pathway in early brain injury induced by subarachnoid hemorrhage. Rats were treated with recombinant human Wnt1 (rhwnt1), small interfering Wnt1 (siwnt1) RNA, and monoclonal antibody of Frizzled1 (anti-Frizzled1) at 48 hours after subarachnoid hemorrhage. Expression levels of Wnt1, Frizzled1, β-catenin, peroxisome proliferator-activated receptor-γ, CD36, and active nuclear factor-κB were examined by western blot assay and immunofluorescence staining. Microglia type conversion and inflammatory cytokine levels in brain tissue were examined by immunofluorescence staining and enzyme-linked immunosorbent assay. Our results show that compared with the sham group, expression levels of Wnt1, Frizzled1, and β-catenin were low and reduced to a minimum at 48 hours, gradually returning to baseline at 1 week after subarachnoid hemorrhage. rhwnt1 treatment markedly increased Wnt1 expression and alleviated subarachnoid hemorrhage-induced early brain injury (within 72 hours), including cortical cell apoptosis, brain edema, and neurobehavioral deficits, accompanied by increasing protein levels of β-catenin, CD36, and peroxisome proliferator-activated receptor-γ and decreasing protein levels of nuclear factor-κB. Of note, rhwnt1 promoted M2-type microglia conversion and inhibited release of inflammatory cytokines (interleukin-1β, interleukin-6, and tumor necrosis factor-α). In contrast, siwnt1 RNA and anti-Frizzled1 treatment both resulted in an opposite effect. In conclusion, the Wnt/Frizzled1 signaling pathway may participate in subarachnoid hemorrhage-induced early brain injury via inhibiting the inflammatory response, including regulating microglia type conversion and decreasing inflammatory cytokine release. The study was approved by the Animal Ethics Committee of Anhui Medical University and First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China (approval No. LLSC-20180202) in May 2017.